👤

Daca an=1/m,an=1/n,m diferit de n,calculati Sm-n

Răspuns :

Răspuns:


Explicație pas cu pas:

[tex]\text{Fie r ratia progresiei.}\\a_n=a_1+(n-1)\cdot r\Rightarrow \dfrac{1}{m}=a_1+(n-1)\cdot r\\\\a_m=a_1+(m-1)\cdot r\Rightarrow \dfrac{1}{n}=a_1+(m-1)\cdot r\\~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~----------\\~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~\dfrac{1}{m}-\dfrac{1}{n}=(n-1)\cdot r-(m-1)\cdot r\\~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~\dfrac{n-m}{m\cdot n}=r(n-1-m+1)\\~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~\dfrac{n-m}{m\cdot n}=r(n-m)|:(n-m)\neq 0\\~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~\boxed{r=\dfrac{1}{m\cdot n}}[/tex]

[tex]\dfrac{1}{m}=a_1+(n-1)\cdot \dfrac{1}{m\cdot n}\\\\a_1=\dfrac{1}{m}-\dfrac{n-1}{m\cdot n}\\\\a_1=\dfrac{n-n+1}{m\cdot n}\\\\\boxed{a_1=\dfrac{1}{m\cdot n}}[/tex]

[tex]a_{m-n}=a_1+(m-n-1)\cdot r\\a_{m-n}=\dfrac{1}{m\cdot n}+(m-n-1)\cdot \dfrac{1}{m\cdot n}\\a_{m-n}=\dfrac{1+m-n-1}{m\cdot n}=\dfrac{m-n}{m\cdot n}[/tex]

[tex]S_{m-n}=\dfrac{(a_1+a_{m-n})\cdot (m-n)}{2}\\\\S_{m-n}=\dfrac{\left(\frac{1}{m\cdot n}+\frac{m-n}{m\cdot n}\right)\cdot(m-n)}{2}\\\\\boxed{S_{m-n}=\dfrac{(1+m-n)(m-n)}{2\cdot m\cdot n}}[/tex]